DIGITAL CITIZENSHIP: AWARENESS, PRESERVATION AND VIRTUAL AND INFORMAL ENVIRONMENTAL EDUCATION (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
This article aims to propose a reflection on the theme of digital citizenship and informal environmental education that can be carried out through activities carried out outside the academic environment, through awareness processes and practices with the participation of communities, social movements, collectives, companies, and associations, as instruments capable of reinforcing the need to participate in the democratization of the environment, aiming at the preservation of natural resources and the various forms of life on the planet. Exposure to the technological transformations of the digital age will contribute to changing the position of a simple spectator, becoming an active actor and component of a globalized and hyper-connected world that inserts him into the concept of digital citizenship. Broad, conscious, critical, and transformative environmental education, which can contribute to the formation of their awareness, providing them with instruments of participation in the protection of the environment in the face of current environmental changes caused by the action of the man himself and those resulting from inadequate exploitation it may be the verifiable result. This awareness through digital citizenship and complimentary access to informal environmental education can contribute to generating critical and reflective social participation that will grant citizens the possibility of transforming the environment, as a way of realizing not only fundamental rights in the pursuit of a dignified life but of the advancement of the whole community.